Information Technology Blue Print Design Using Enterprise Architecture Planning in Politeknik Negeri Bali - I Ketut Suja; Gede Rasben Dantes; Gede Indrawan (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
The Information Technology (IT) blueprint basically contains a strategic plan of the company / institution in implementing and developing information technology / information systems in the company / institution. This study aims to design the IT Blueprint model in terms of data architecture, application architecture and technology architecture using the Zachman Framework enterprise architecture, where the blueprint is a comprehensive and integrated information technology system design. The methodology used in this study refers to the framework of Enterprise Architecture Planning. The results of this study obtained data architecture design, applications and technology along with data entities, business entities and business processes and business process functions so that they can illustrate the IT blueprint model along with the implementation roadmap that serves as a reference and guideline campus of Politeknik Negeri Bali (PNB).